Pemanfaatan Tanaman Pangan dalam Upacara Adat Saur Matua Suku Batak Toba Kecamatan Nainggolan Kabupaten Samosir Sumatra Utara - Elisabeth Siregar; Dina Handayani (Jurnal Biosilampari : Jurnal Biologi, 2026)
The research aims to document and analyze the ethnobotanical utilization of food crops within the Saur Matua traditional ceremony of the Toba Batak tribe in Nainggolan District, Samosir Regency. Utilizing a qualitative descriptive approach, data were collected through semi-structured interviews with fourteen informants and field observations in Sibonor Ompu Ratus and Sinaga Uruk Pandiangan villages. The study identified 26 species of food plants belonging to 17 families, with Zingiberaceae, Solanaceae, and Amaryllidaceae being the most dominant. The findings reveal that the fruit is the most frequently utilized plant part, while the herb habitus is the most common growth form. These plants are primarily processed as cooking spices for traditional dishes like dekke arsik and saksang, as well as ceremonial snacks like lapet. Beyond nutritional value, these plants carry profound philosophical meanings; for instance, eme (rice) symbolizes prosperity and life continuity. The study concludes that while the Saur Matua ceremony remains a vital cultural pillar, there is a growing dependency on commercial markets for ritual plants due to declining local cultivation. This documentation serves as a crucial effort in preserving the traditional ecological knowledge and cultural identity of the Toba Batak community against the pressures of modernization.